Optimization of Ultra-Wideband bandwidth for the design of microstrip monopole antennas using Defected Ground Structure and star-shaped patche - Muhammad Darsono; Muhammad Rega (Universitas Mercu Buana, 2023)
This paper presents a design of a monopole microstrip antenna developed to support Ultra-wideband (3.1 -10.6 GHz) technology wireless communication systems. An antenna with minimalist dimensions operates on C-Band (wireless LAN) and X-Band (downlink satellite) frequencies. The antenna profile has a star shape patch on the top side and the use of the Defected Ground Structure (DGS) technique on the bottom side on RT DUROID substrate media. The design uses a simulation method using software and measurement tests on antenna prototypes to obtain parameters and antenna performance characteristics. The results of the measurement test, the bandwidth return loss < -10 dB has a difference of 40% (absolute) and 0.7% (Fractional) lower than the simulation when VSWR < 2. The radiation pattern forms an omnidirectional with a maximum directivity (Gain) of 5.18dBi with polarization vertical. Overall, the UWB monopole antenna design results have a low profile, compact, small size, and support mobile communication devices.